BS EN 2996-006. Aerospace series. Circuit breakers, three-poles, temperature compensated, rated currents 1 A to 25 A. Part 006. 6, 3 & 2, 8 mm blade terminal. With polarized signal contact. Product standard (19th July 2021) - British Standards Institution,
No abstract available